PERANCANGAN DAN IMPLEMENTASI SISTEM KEHADIRAN DOSEN MENGGUNAKAN TEKNOLOGI FINGERPRINT PADA STTI NIIT I-TECH - Saputra, Asri Hayat; Efendi, Yasin; Fatimah, Julia (Jurnal Ilmiah Sistem Informasi, 2024)
Lecturer attendance system on STTI NIIT I-Tech campus is still managed manually used the notebook of lecture realization. This wasn’t rule out errors in managing attendance data, loss of attendance data and lecturer cheating in counterfeit their presence. From the problem, then made the attendance system by using fingerprint technology where the secretariat record all the lecturer’s attendance data in the system. The lecturer’s attendance data collection is done by recording fingerprint on the fingerprint scanner machine. In the end the result obtained is a lecturer’s attendance system using fingerprint technology on web-based STTI NIIT I-Tech by using local network